"Time and Tide" : the feminist and cultural politics of a modern magazine - Clay, Catherine, 1971- (Edinburgh University Press Ltd, 2018)
"The first in-depth study of the landmark modern feminist magazine, "Time and Tide." Unique in establishing itself as the only female-run intellectual weekly in the golden age of the weekly review, "Time and Tide" both challenged persistent prejudices against women's participation in public life and played an instrumental role in redefining women's gender roles and identities. Drawing on extensive new archival research, Catherine Clay recovers the contributions to this magazine of both well- and lesser-known British women writers, editors, critics and journalists and explores a cultural dialogue about literature, politics and the arts that took place beyond the parameters of modernist 'little magazines.' The book makes a major contribution to the history of women's writing and feminism in Britain between the wars."--Publisher's description
Keywords: Time and tide.; Time and tide; Women's periodicals, English -- History -- 20th century.; Women's periodicals, English -- Social aspects.; Women's periodicals, English -- Political aspects.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Women's periodicals, English; Women's periodicals, English -- Social aspects; 1900-1999; Electronic books.; History